Pengaruh Pemberian Ekstrak Teh Hijau (Cammelia Sinensis) Terhadap Gambaran Histopatologi Silia Pada Trakea Tikus Putih Jantan Galur Sprague Dawley yang Dipapar Uap Rokok Elektronik - Ahmad Syah Putra; Susianti; Rizki Hanriko (Medula, 2021)
At present, there is a shift in the use of cigarettes, from conventional cigarettes to e-cigarettes. Exposure to particulate e-cigarettes can cause damage to the airway, one of which is ciliary tracheal. Green tea (Camellia sinensis) has a source of antioxidants in the form of polyphenols which can reduce the number of organ damage through a mechanism as an anti-oxidant. The study used an experimental design using 30 Sprague Dawley strain white rats which were divided into 6 groups, namely 3 control groups and 3 treatment groups. In the control group, given regular treatment, exposure to electric cigarettes and exposure to conventional cigarettes. In the treatment group, mice were given peritoneal injection of green tea extract each of 50 mg/kg body weight, 100 mg/kg body weight, and 200 mg/kg body weight. After 14 days of treatment, the 15th day of mice was euthanized and preparations were taken. There was a change in histopathological damage in all samples where there were significant differences in the control group, but not significantly in the treatment group with a value of K1 to K2 with p = 0.005, and K1 to K3 with p = 0.007. Whereas in vape control group (K2) between treatment groups P1, P2, and P3 were p = 0.521.There is not difference between the administration of green tea extract to histological ch es in cilia’s tracheal structure of rats exposed to steam electronic cigarettes with p=0,521.